Cutis Verticis Gyrata in Men Affected by HIV-Related Lipodystrophy - Keshav Khanijow; Patrick Unemori; Kieron S. Leslie; Kathleen Mulligan; Morris Schambelan; Toby Maurer (Dermatology Research and Practice)
We report the occurrence of cutis verticis gyrata (CVG), a disfiguring dermatological condition, in four patients with HIV-related lipodystrophy (HIVLD). These four patients had abnormal metabolic and hormonal lab values which we compare with metabolic and hormonal perturbations cited in previous HIVLD cohorts. In addition, we describe the sole use of poly-L-lactic acid as a potential treatment for decreasing the appearance of CVG-associated ridges.